Proceedings of the 2017 5th International Conference on Machinery, Materials and Computing Technology (ICMMCT 2017) 2017
DOI: 10.2991/icmmct-17.2017.92
|View full text |Cite
|
Sign up to set email alerts
|

Investigation and analysis on the illumination of the university classroom

Abstract: Abstract. Appropriate classroom lighting environment in universities should be able to meet the needs of the students physical and mental, and it has the practical significance to improve the student' vision, physical and mental health and learning efficiency. The paper uses the subjective and objective research method to investigate and analyse the present illumination situation of the university classroom based on the national standard of the :GB50034-2013. According … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Many of the studies on lighting similar to the present one found in the available literature were conducted using DIALux ® [8,[19][20][21][22][23], although it seems that there are many possibilities when it comes to lighting simulation tools [26][27][28][29]. However, leaving aside some works related to validation of lighting analysis software [30][31][32][33], there seems to be a lack of studies evaluating the accuracy in the prediction of actual lighting results.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…Many of the studies on lighting similar to the present one found in the available literature were conducted using DIALux ® [8,[19][20][21][22][23], although it seems that there are many possibilities when it comes to lighting simulation tools [26][27][28][29]. However, leaving aside some works related to validation of lighting analysis software [30][31][32][33], there seems to be a lack of studies evaluating the accuracy in the prediction of actual lighting results.…”
Section: Introductionmentioning
confidence: 88%
“…The importance of proper lighting conditions (i.e., visual comfort) at academic institutions has been emphasized at all levels, from elementary, primary, and secondary education schools [1][2][3][4][5][6] to university faculties [7][8][9][10][11][12][13][14][15][16]. In general, it can be said that comfort in academic environments has been widely analyzed as it has important effects on learning.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation